2009
DOI: 10.1080/08858190902973143
|View full text |Cite
|
Sign up to set email alerts
|

Oncology Education in Canadian Undergraduate and Postgraduate Training Programs

Abstract: Oncology is underrepresented in current curriculums.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 21 publications
(19 reference statements)
3
28
1
1
Order By: Relevance
“…Our results confirm the findings of an earlier, smaller study of administrators in charge of Canadian undergraduate schools of medicine, nursing, pharmacy, and postgraduate resident training programs 3 . The education leaders in that study also believed that the level of oncology education in their respective programs at that time was inadequate.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our results confirm the findings of an earlier, smaller study of administrators in charge of Canadian undergraduate schools of medicine, nursing, pharmacy, and postgraduate resident training programs 3 . The education leaders in that study also believed that the level of oncology education in their respective programs at that time was inadequate.…”
Section: Discussionsupporting
confidence: 82%
“…We were not able to obtain responses from educators and learners in all Canadian medical schools and residency training programs. Response rates from certain groups of educators and learners in the medical training programs that we were able to survey were lower than those in other studies 3,12 . Response rates from umeccms and oncologists were lower because we were not allowed to contact those groups directly and had to rely on a third party to forward the survey link and subsequent reminder message.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…9 Ten of 11 (90.9%) pharmacy colleges and schools responded, with 80% of pharmacy responders spending 1 week or less on cancer education. Only 30% of these institutions required cancer education, only 20% offered an elective course for cancer education, and 70% reported mentioning cancer treatment only a few times throughout their program.…”
Section: Introductionmentioning
confidence: 99%
“…2 Despite these responsibilities, studies have shown that there is a deficiency in focused oncology teaching during medical school in Canada and the United Kingdom and many other European countries. [3][4][5][6][7] Our recent national survey showed that most educators and learners believe oncology education in Canadian family medicine and internal medicine training programs at both the undergraduate and postgraduate levels is inadequate. 4 When comparing the teaching of disease related to 10 different medical subspecialties, the educators and learners agreed that oncology was the most poorly taught to medical students.…”
mentioning
confidence: 99%